La mirada del viajero: sus dibujos - Correa Gómez, Analía Zulema (2018)
The traveling architect captures the essence of the place through the sketch. Walk, look and see ...affected by sounds, colors and textures. Walk and feel, walk and draw, and in his drawing he expresses his feelings. "Click": that's a second, "click, click": that's been two seconds. The places that the traveler walks are wonderful. Surely they deserve more than two seconds of attention. When you sketch your impressions of a new city, it is typical of the nature of the drawing that you dedicate more time to your motive than the time it takes to take a picture.